Government’s Legal Responsibility Upon Entrepreneur’s Economic Loss Caused by the Failure in Implementing the Legislation Regarding Business Licensing and Registration - S, Sujana Donandi (Jurnal Suara Hukum, 2019)
The Regulation of Minister of Trade No. 14 Year 2016 (Permendag 14/2016) Regarding Trading Business License (SIUP) and Company Registration ID (TDP) states that SIUP and TDP should be issued no longer than 2 working days. However, This regulation failed to be implemented by Regional Government of Kabupaten Bekasi when PT. EIM managed their SIUP and TDP in five working days. It caused economic losses for PT. EIM because they need the documents as a requirement to earn training project worthed Rp. 50.000.000. This research tried to examine the government’s responsibility upon entrepreneur’s economic loss caused by the failure in implementing the legislation regarding Business Licensing and Registration. The methodology used in this research is Normative-Empirical Legal Research. Normative-Empirical Legal Research is a research which the object including the legislation (in abstracto) and its implementation at the concrete situation. The Result showed that the economic loss gained by PT. EIM is the responsibility of Regional Government of Kabupaten Bekasi since their failure to issue SIUP and TDP on time is a tort. As result, every party committed to tort have to pay compensation. Form of the compensation consists of material and immaterial compensation. To apply the compensation, PT. EIM could follow the non-litigation and litigation procedures.